PENGEMBANGAN MODEL PEMBELAJARAN IPS BERBASIS NILAI SIMBOLISME KAIN SONGKET UNTUK MENINGKATKAN SOLIDARITAS SOSIAL SISWA SMP NEGERI 6 KAYUAGUNG - Kurniawan, Bayu; Sariyatun, S.; Joebagio, Hermanu (Sebelas Maret University (UNS), 2017)
Indonesia as an archipelagic country store who so abundant in culture.This wealth can be seen from the kebudaya of literary work, building, objects history, works of art and others.The results of culture, Songket is one of culture. Songket is the result culture the community malay especially the people of south Sumatra who still stay there until now. On each motive, having symbols containing values local knowledge especially in form of social solidarity in society south Sumatra. Values local knowledge this needs implementation in students in learning especially on the subjects of social science class in Junior High School.Thus developed a learning model social class based value Songket symbolism to increse of social solidarity students in Junior High School Â 6 Kayuagung. Research and development is organized based on the concept of that has been created by borg and gall. Implementation phase in this research include study introduction, the development of learning model, and the effectiveness model. Data analysis use scale lingkert by the span of 5 while test the effectiveness of model use T test.In T test obtained value 3,789 with significance 0,000 & lt; 0,025, it means is the a significant impact on the model developed.While test t for the judgment of attitude of social solidarity with the economic situation of 2,360 significance much as 0.021 & lt; 0,025, so that rerata before and sesusah treatment class experiment not at.Thus learning model social class developed effective to improve their performance and attitude of social solidarity of student.